Corrosion-resistant equal-strength deformed steel bar type resin anchor rod metal rod body and preparation process thereof

Through the process of shooting blasting, zinc seepage, passivation and coating composite coating, the corrosion problem of equal-strong rebar anchors in harsh environments is solved, and its corrosion resistance and service life are significantly improved.

CN119320924APending Publication Date: 2025-01-17SHANDONG RONGLIANG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411367705.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The strong rebar anchors are susceptible to corrosion in complex natural environments, resulting in degradation of material performance and structural failure. The existing technology is difficult to effectively solve their corrosion resistance problems.

Method used

The anchor metal rod body is treated with shot blasting, zinc seepage, passivation and coating composite anticorrosion coating to form a multi-layer protective barrier to enhance its corrosion resistance. Specific steps include shot blasting to remove the oxide scale, zinc-permeable iron alloy layer, passivation to form a dense oxide film, and coating the surface with a composite coating of nanoparticles and silicon nitride modified resin.

Benefits of technology

It significantly improves the corrosion resistance and service life of equal-strong rebar anchors, while maintaining their mechanical properties, extending the safety and durability of the structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119320924A_ABST
    Figure CN119320924A_ABST
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant equal-strength deformed steel bar type resin anchor rod metal rod body and a preparation process thereof, and belongs to the technical field of resin anchor rods. Shot blasting treatment is carried out on an anchor rod metal rod body workpiece, oxide skin, corrosion and oil dirt on the surface of the rod body are effectively removed, a clean anchor rod metal rod body is obtained, zinc impregnation treatment and passivation treatment are further carried out on the clean anchor rod metal rod body, and two layers of compact protection barriers are formed; and finally, the surface of the passivated anchor rod metal rod body is coated with composite anticorrosive paint, and the corrosion-resistant equal-strength deformed steel bar type resin anchor rod metal rod body is obtained. The corrosion resistance of the metal rod body is improved, and the original mechanical property of the metal rod body is kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of resin anchor rods, and in particular relates to a corrosion-resistant and iso-strong threaded steel resin anchor rod metal rod body and a preparation process thereof. Background Art

[0002] In modern engineering construction, especially in infrastructure fields such as mines, tunnels, bridges, and buildings, anchor rods are an important connection and reinforcement material, and their performance is directly related to the safety and durability of the entire structure. As one of the main materials for anchor rods, equal-strength threaded steel is widely used due to its high strength, good processing performance and relatively economical cost. However, in complex and changeable natural environments, such as oceans, saline-alkali land, and humid areas, equal-strength threaded steel is susceptible to corrosion by corrosive media such as salt spray, moisture, and oxygen, resulting in a decrease in material performance and even structural failure.

[0003] The corrosion of iso-strength threaded steel is mainly an electrochemical process involving electron transfer between the metal surface and the surrounding medium. In a salt spray environment, chloride ions can penetrate the oxide film on the metal surface and form soluble metal chlorides with the metal matrix, accelerating the corrosion process. At the same time, moisture and oxygen, as necessary conditions for corrosion reactions, also promote the corrosion reaction. In addition, factors such as microscopic defects, impurities and stress concentration on the metal surface will also aggravate the occurrence of corrosion. Therefore, the development of an iso-strength threaded steel resin anchor metal rod body with excellent corrosion resistance is of great significance to improving the safety of engineering structures and extending their service life. Summary of the invention

[0004] The object of the present invention is to provide a corrosion-resistant and iso-strong threaded steel resin anchor metal rod body and a preparation process thereof, so as to solve the technical problem that the anchor metal rod body is not corrosion-resistant in harsh environments in the prior art.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention provides a method for preparing a corrosion-resistant and iso-strong threaded steel resin anchor metal rod body, comprising the following steps:

[0007] (1) Steel pretreatment: Select the anchor metal rod steel, cut it and cut out the sharp corners to obtain the anchor metal rod workpiece;

[0008] (2) Shot blasting: Put the anchor metal rod workpiece into the shot blasting machine for shot blasting to obtain a clean anchor metal rod body;

[0009] (3) Sherardizing treatment: the clean anchor metal rod body is placed in a sherardizing furnace and sherardized by powder sherardizing. After cooling, the metal rod body is taken out of the furnace to obtain a sherardized anchor metal rod body.

[0010] (4) Passivation treatment: The zinc-plated anchor metal rod body is transported to the automatic spray cleaning area for cleaning, and then moved to the passivation area for passivation treatment. After the passivation treatment is completed, the residual passivation liquid is removed to obtain a passivated anchor metal rod body;

[0011] (5) Applying a composite anti-corrosion coating: Applying a composite anti-corrosion coating on the surface of the passivated anchor metal rod body to obtain a corrosion-resistant and strong threaded steel resin anchor metal rod body.

[0012] Furthermore, in step (2), the shot blasting machine is of a through-type, the diameter of the steel shot used is 0.8 to 1.2 mm, the shot blasting time is 20 to 30 min, and the surface cleanliness of the clean anchor metal rod body reaches Sa3 level.

[0013] Furthermore, step (3) is specifically as follows:

[0014] S1. Add filler: put the clean anchor metal rod into the sherardizing furnace, and then add the filler into the sherardizing furnace for embedding;

[0015] S2. Adding the zincizing agent: Add zinc powder into the zincizing furnace and stir evenly;

[0016] S3. High temperature zinc infiltration: Sprinkle the infiltration agent evenly into the zinc infiltration furnace and then seal the furnace, set the furnace temperature, and after the reaction is completed, cool down and take the zinc infiltration anchor metal rod body out of the furnace to obtain.

[0017] Furthermore, the filler in S1 is one or both of quartz sand and alumina, and the volume of the added filler accounts for 35-40% of the volume of the zincizing furnace; the zinc powder in S2 is added at a ratio of 20-22 kg / T of workpiece weight and stirred for 30-40 minutes; the penetration aid in S3 is ammonium chloride, and ammonium chloride is added at a ratio of 0.3-0.35 kg / T, the furnace temperature is set to 450-480°C, and the timing and insulation start when the furnace temperature reaches 380°C, the insulation time is 4-5 hours, and the furnace is taken out when the temperature drops to 60-100°C.

[0018] Furthermore, in step (4), the spraying time is 10 to 40 minutes, the pH value of the passivation solution is 10 to 12, the temperature of the passivation solution is 5 to 35° C., and the passivation time is 60 to 300 seconds.

[0019] Furthermore, step (5) is specifically as follows:

[0020] Q1. Pretreatment of nanoparticles: put the nanoparticles into a flask, add silane coupling agent KH-570 in the presence of anhydrous ethanol, stir under water bath conditions, filter and wash, put into a constant temperature dryer for drying, and after completion, obtain modified nanoparticles;

[0021] Q2. Silicon nitride pretreatment: Add silicon nitride to a beaker, stir evenly in the presence of isopropanol, then add silane coupling agent KH-570, stir in a water bath to completely evaporate the isopropanol, filter and wash, and put into a constant temperature dryer to dry, and after completion, modified silicon nitride is obtained;

[0022] Q3. Mixing uniformly: Weigh the modified nanoparticles and modified silicon nitride into a beaker, add anhydrous ethanol at the same time, perform ultrasonic treatment, and after uniform dispersion, weigh the polyurethane resin and add it into a beaker, perform ultrasonic treatment, then add the silicone resin into the beaker and stir uniformly, continue ultrasonic treatment, and mix uniformly to obtain a homogeneous reaction liquid;

[0023] Q4. Add curing agent: add catalyst to the homogeneous reaction liquid, stir evenly, then add curing agent, stir evenly to obtain liquid composite anti-corrosion coating;

[0024] Q5. Coating treatment: Coat the composite anti-corrosion coating on the surface of the passivated anchor metal rod body, and after drying, obtain a corrosion-resistant and strong threaded steel resin anchor metal rod body.

[0025] Furthermore, the nanoparticles in Q1 are a mixture of nano-silicon dioxide and nano-alumina, the mass ratio of nano-silicon dioxide to nano-alumina is 2:1, the amount of anhydrous ethanol added is 10 to 15 times the volume of the nanoparticles, the amount of silane coupling agent KH-570 added is 1 to 10 mL, the water bath temperature is 70 to 75°C, the stirring speed is 200 to 250 r / min, the time is 4 to 6 hours, anhydrous ethanol is used for washing, the dryer temperature is set to 70 to 80°C, and the drying time is 24 to 30 hours; in Q2, the mass ratio of silicon nitride added to the nanoparticles is 2:1, the amount of silane coupling agent KH-570 added is 1 to 10 mL, the water bath temperature is 70 to 75°C, the stirring speed is 200 to 250 r / min, the time is 4 to 6 hours, anhydrous ethanol is used for washing, the dryer temperature is set to 70 to 80°C, and the drying time is 24 to 30 hours. The temperature is set to 70-80°C, and the drying time is 24-30 hours; the amount of anhydrous ethanol added in Q3 is 1-5 times the volume of the modified nanoparticles and modified silicon nitride, the frequency of ultrasonic treatment is 200-300 Hz, the time is 30-60 min, the amount of polyurethane resin added is 1-3 times the mass of nanoparticles and silicon nitride, and the amount of silicone resin added is 0.8-2 times the mass of nanoparticles and silicon nitride; the catalyst in Q4 is dibutyltin dilaurate, the mass ratio of the catalyst added to the polyurethane resin is 1:5-10, the curing agent is isocyanate curing agent, the mass ratio of the curing agent added to the polyurethane resin is 1:1-2, and the curing time is 2-6 hours; the coating method in Q5 is spraying, the coating thickness is 100-150 μm, and the drying time is 18-24 hours.

[0026] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0027] 1. The present invention can effectively remove the oxide scale, rust and oil on the surface of the anchor rod by shot blasting the anchor rod metal rod workpiece, which not only cleans the surface, but also makes the metal surface microscopically rougher due to the tiny bumps and grooves, thereby increasing the adhesion of the subsequent coating. The zinc infiltration treatment and passivation treatment form a multi-layer protective barrier to prevent corrosion, and the coating of the composite anti-corrosion coating further enhances the protection, thereby improving the corrosion resistance of the metal rod body and maintaining its original mechanical properties.

[0028] 2. The present invention modifies nanoparticles and silicon nitride. The modified nanoparticles and silicon nitride enhance the compatibility and dispersibility with the resin matrix, which helps to improve the mechanical properties and corrosion resistance of the coating. The polyurethane resin has excellent mechanical properties and weather resistance, and the silicone resin has excellent high and low temperature resistance and chemical corrosion resistance. The coating is transformed from liquid to solid through a curing reaction to form a dense and continuous coating, which can effectively isolate corrosive media such as salt spray and moisture, and significantly improve the corrosion resistance of equal-strength threaded steel. At the same time, the coating also enhances its wear resistance and weather resistance, which can effectively extend the service life of equal-strength threaded steel.

[0029] 3. The present invention uses powder zinc infiltration to treat the clean anchor metal rod body. At high temperature, zinc atoms and the steel matrix form a zinc-iron alloy layer. Zinc acts as a sacrificial anode to protect the steel matrix from corrosion. At the same time, the hardness of the metal zinc layer is higher than that of steel, which enhances the wear resistance of the surface. Further, a dense oxide film is formed on the surface of the equal-strength threaded steel through a passivation reaction. This film can effectively prevent the penetration of corrosive media and further improve the corrosion resistance of the equal-strength threaded steel. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 The present invention is a preparation flow chart of a method for preparing a corrosion-resistant and iso-strength threaded steel resin anchor metal rod body. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The metal rod used in the present invention is: MSGLD-400 / 22*2250, implemented in accordance with the standard MT146.2-2011; the steel material is: MG400Y, implemented in accordance with the standard YB / T 4364-2014. The rod length deviation is: ±10; the straightness is ≤2mm / m.

[0034] Embodiment 1:

[0035] This embodiment provides a method for preparing a corrosion-resistant and iso-strong threaded steel resin anchor metal rod body, the method comprising the following steps:

[0036] (1) Pretreatment: Select 1T anchor metal rod steel, cut it and cut out the sharp corners to obtain the anchor metal rod workpiece;

[0037] (2) Shot blasting: The anchor metal rod body is placed in a through-type shot blasting machine for shot blasting. The diameter of the steel shot is 0.8 mm and the shot blasting time is 20 min. After the shot blasting, the surface cleanliness of the equal-strength threaded steel reaches Sa3 level. When observed without magnification, the surface has a uniform metallic luster, and a clean anchor metal rod body is obtained.

[0038] (3) Sherardizing treatment: the clean anchor metal rod body is placed in a sherardizing furnace and sherardized by powder sherardizing. After cooling, the metal rod body is taken out of the furnace to obtain a sherardized anchor metal rod body.

[0039] (4) Passivation treatment: The zinc-plated anchor metal rod body is transported to the automatic spray cleaning area for 10 minutes to remove surface dust and residual penetrant, and then moved to the passivation area. The passivation liquid is purchased from Liaocheng Demei Technology Co., Ltd. The pH value of the passivation liquid is 10, the temperature of the passivation liquid is 5°C, and the passivation time is 60 seconds. After the treatment, the residual passivation liquid is removed to obtain the passivated anchor metal rod body;

[0040] (5) Applying a composite anti-corrosion coating: A composite anti-corrosion coating is applied to the surface of the passivated anchor metal rod body to obtain a corrosion-resistant and strong threaded steel resin anchor metal rod body.

[0041] Specifically, in step (3), the operation steps are as follows:

[0042] S1. Adding fillers: first add clean anchor metal rod body into the sherardizing furnace, then add quartz sand, the volume of the added quartz sand accounts for 35% of the volume of the sherardizing furnace, and obtain embedded equal-strength threaded steel bar;

[0043] S2. Adding a penetrating agent: Add 20 kg of zinc powder to the zincizing furnace, stir the zinc powder and the embedded equal-strength threaded steel for 30 to 40 minutes to obtain the equal-strength threaded steel to be infiltrated;

[0044] S3. High temperature zincizing: weigh 0.3kg of ammonium chloride, sprinkle it evenly into the zincizing furnace and seal the furnace. Set the furnace temperature to 450℃. When the furnace temperature reaches 380℃, start the heat preservation time for 4 hours. After the reaction is completed, take it out of the furnace when the temperature drops to 100℃ to obtain the zincizing anchor metal rod body.

[0045] Step (5) includes the following steps:

[0046] Q1. Pretreatment of nanoparticles: weigh 6g of nano-silica and 3g of nano-alumina and put them into a flask, add 100mL of anhydrous ethanol, add 2mL of silane coupling agent KH-570 in the presence of anhydrous ethanol, stir at a water bath temperature of 70°C, at a stirring speed of 200r / min, for 4 hours, filter, wash with anhydrous ethanol, and dry in a constant temperature dryer, the dryer temperature is set to 70°C, and the drying time is 30 hours to obtain modified nanoparticles;

[0047] Q2. Silicon nitride pretreatment: weigh 18g of silicon nitride and add it to a beaker. Add 200mL of isopropanol to the beaker, stir evenly in the presence of isopropanol, and then add 2mL of silane coupling agent KH-570 to the beaker. Stir at a water bath temperature of 70°C and a stirring speed of 200r / min for 4h. Volatilize the isopropanol completely, filter, wash with anhydrous ethanol, and then put it into a constant temperature dryer for drying. The dryer temperature is set to 70°C. After drying for 30 hours, modified silicon nitride is obtained.

[0048] Q3, uniform mixing: weigh 5g of modified nanoparticles and 10g of modified silicon nitride and add them to a beaker, add 20mL of anhydrous ethanol at the same time, perform ultrasonic treatment, the frequency of ultrasonic treatment is 200Hz, the time is 30min, after uniform dispersion, weigh 15g of polyurethane resin and add it to a beaker, then perform ultrasonic treatment, the frequency of ultrasonic treatment is 200Hz, the time is 30min, then add 12g of silicone resin to the beaker and stir evenly, continue ultrasonic treatment, the frequency of ultrasonic treatment is 200Hz, the time is 30min, and after uniform mixing, a homogeneous reaction liquid is obtained;

[0049] Q4. Add curing agent: add 2g of dibutyltin dilaurate as a reaction catalyst to the homogeneous reaction liquid, stir evenly, add 7.5g of isocyanate curing agent, stir evenly to obtain a liquid composite anti-corrosion coating, and apply it immediately;

[0050] Q5. Coating treatment: spray the composite anti-corrosion coating on the surface of the passivated anchor metal rod with a coating thickness of 100 μm. After drying for 18 hours, a corrosion-resistant and strong threaded steel resin anchor metal rod is obtained.

[0051] Embodiment 2:

[0052] This embodiment provides a method for preparing a corrosion-resistant and iso-strong threaded steel resin anchor metal rod body, the method comprising the following steps:

[0053] (1) Pretreatment: Select 1T anchor metal rod steel, cut it and cut out the sharp corners to obtain the anchor metal rod workpiece;

[0054] (2) Shot blasting: The anchor metal rod body is placed in a through-type shot blasting machine for shot blasting. The diameter of the steel shot is 1 mm and the shot blasting time is 30 min. After the shot blasting, the surface cleanliness of the equal-strength threaded steel reaches Sa3 level. When observed without magnification, the surface has a uniform metallic luster, and a clean anchor metal rod body is obtained.

[0055] (3) Sherardizing treatment: the clean anchor metal rod body is placed in a sherardizing furnace and sherardized by powder sherardizing. After cooling, the metal rod body is taken out of the furnace to obtain a sherardized anchor metal rod body.

[0056] (4) Passivation treatment: The zinc-plated anchor metal rod body is transported to the automatic spray cleaning area for 10 to 40 minutes to remove surface dust and residual penetrant, and then moved to the passivation area. The passivation liquid is purchased from Liaocheng Demei Technology Co., Ltd. The pH value of the passivation liquid is 11.2, the temperature of the passivation liquid is 25°C, and the passivation time is 120 seconds. After the treatment, the residual passivation liquid is removed to obtain the passivated anchor metal rod body;

[0057] (5) Applying a composite anti-corrosion coating: A composite anti-corrosion coating is applied to the surface of the passivated anchor metal rod body to obtain a corrosion-resistant and strong threaded steel resin anchor metal rod body.

[0058] Specifically, in step (3), the operation steps are as follows:

[0059] S1. Adding fillers: first add clean anchor metal rod body into the sherardizing furnace, then add quartz sand, the volume of the added quartz sand accounts for 37% of the volume of the sherardizing furnace, and obtain embedded equal-strength threaded steel bar;

[0060] S2. Adding a penetrating agent: Add 21 kg of zinc powder to the zincizing furnace, stir the zinc powder and the embedded equal-strength threaded steel for 35 minutes to obtain the equal-strength threaded steel to be infiltrated;

[0061] S3. High temperature zincizing: weigh 0.32kg of ammonium chloride, sprinkle it evenly into the zincizing furnace and seal the furnace, set the furnace temperature to 470℃, start timing and keep warm when the furnace temperature reaches 380℃, the insulation time is 4.5 hours, after the reaction is completed, wait until the temperature drops to 80℃ and take it out of the furnace to obtain the zincizing anchor metal rod body.

[0062] Step (5) includes the following steps:

[0063] Q1. Pretreatment of nanoparticles: weigh 6g of nano-silica and 3g of nano-alumina and put them into a flask, add 100mL of anhydrous ethanol, add 5mL of silane coupling agent KH-570 in the presence of anhydrous ethanol, stir at a water bath temperature of 72°C, at a stirring speed of 220r / min, for 5 hours, filter, wash with anhydrous ethanol, and dry in a constant temperature dryer, the dryer temperature is set to 75°C, and the drying time is 28 hours to obtain modified nanoparticles;

[0064] Q2. Silicon nitride pretreatment: weigh 18g of silicon nitride and add it to a beaker. Add 200mL of isopropanol to the beaker, stir evenly in the presence of isopropanol, and then add 2mL of silane coupling agent KH-570 to the beaker. Stir at a water bath temperature of 75°C and a stirring speed of 230r / min for 5h. Volatilize the isopropanol completely, filter, wash with anhydrous ethanol, and then put it into a constant temperature dryer for drying. The dryer temperature is set to 75°C. After drying for 28 hours, modified silicon nitride is obtained.

[0065] Q3, uniform mixing: weigh 5g of modified nanoparticles and 10g of modified silicon nitride into a beaker, add 20mL of anhydrous ethanol at the same time, perform ultrasonic treatment, the frequency of ultrasonic treatment is 250Hz, the time is 45min, after uniform dispersion, weigh 25g of polyurethane resin into a beaker, then perform ultrasonic treatment, the frequency of ultrasonic treatment is 250Hz, the time is 45min, then add 15g of silicone resin into the beaker and stir evenly, continue ultrasonic treatment, the frequency of ultrasonic treatment is 250Hz, the time is 45min, and after uniform mixing, a homogeneous reaction liquid is obtained;

[0066] Q4. Add curing agent: add 3g of dibutyltin dilaurate as a reaction catalyst to the homogeneous reaction liquid, stir evenly, add 10g of isocyanate curing agent, stir evenly to obtain a liquid composite anti-corrosion coating, and apply it immediately;

[0067] Q5. Coating treatment: spray the composite anti-corrosion coating on the surface of the passivated anchor metal rod with a coating thickness of 120μm. After drying for 20 hours, a corrosion-resistant and strong threaded steel resin anchor metal rod is obtained.

[0068] Embodiment 3:

[0069] This embodiment provides a method for preparing a corrosion-resistant and iso-strong threaded steel resin anchor metal rod body, the method comprising the following steps:

[0070] (1) Pretreatment: Select 1T anchor metal rod steel, cut it and cut out the sharp corners to obtain the anchor metal rod workpiece;

[0071] (2) Shot blasting: The anchor metal rod body is placed in a through-type shot blasting machine for shot blasting. The diameter of the steel shot is 1.2 mm and the shot blasting time is 30 min. After the shot blasting, the surface cleanliness of the equal-strength threaded steel reaches Sa3 level. When observed without magnification, the surface has a uniform metallic luster, and a clean anchor metal rod body is obtained.

[0072] (3) Sherardizing treatment: the clean anchor metal rod body is placed in a sherardizing furnace and sherardized by powder sherardizing. After cooling, the metal rod body is taken out of the furnace to obtain a sherardized anchor metal rod body.

[0073] (4) Passivation treatment: The zinc-plated anchor metal rod body is transported to the automatic spray cleaning area for 40 minutes to remove surface dust and residual penetrant, and then moved to the passivation area. The passivation liquid is purchased from Liaocheng Demei Technology Co., Ltd. The pH value of the passivation liquid is 12, the temperature of the passivation liquid is 35°C, and the passivation time is 300 seconds. After the treatment, the residual passivation liquid is removed to obtain the passivated anchor metal rod body;

[0074] (5) Applying a composite anti-corrosion coating: A composite anti-corrosion coating is applied to the surface of the passivated anchor metal rod body to obtain a corrosion-resistant and strong threaded steel resin anchor metal rod body.

[0075] Specifically, in step (3), the operation steps are as follows:

[0076] S1. Adding fillers: first add clean anchor metal rod body into the sherardizing furnace, then add quartz sand, the volume of the added quartz sand accounts for 40% of the volume of the sherardizing furnace, and obtain embedded equal-strength threaded steel bar;

[0077] S2. Adding a penetrant: Add 22 kg of zinc powder to the zincizing furnace, stir the zinc powder and the embedded equal-strength threaded steel for 40 minutes to obtain the equal-strength threaded steel to be infiltrated;

[0078] S3. High temperature zincizing: weigh 0.35kg of ammonium chloride, sprinkle it evenly into the zincizing furnace and seal the furnace, set the furnace temperature to 480℃, start the heat preservation timing when the furnace temperature reaches 380℃, and the heat preservation time is 5 hours. After the reaction is completed, wait until the temperature drops to 60℃ and take it out of the furnace to obtain the zincizing anchor metal rod body.

[0079] Step (5) includes the following steps:

[0080] Q1. Pretreatment of nanoparticles: weigh 6g of nano-silica and 3g of nano-alumina and put them into a flask, add 100mL of anhydrous ethanol, add 2mL of silane coupling agent KH-570 in the presence of anhydrous ethanol, stir at a water bath temperature of 75°C, at a stirring speed of 250r / min, for 6 hours, filter, wash with anhydrous ethanol, and dry in a constant temperature dryer, the dryer temperature is set to 80°C, and the drying time is 24 hours to obtain modified nanoparticles;

[0081] Q2. Silicon nitride pretreatment: weigh 18g of silicon nitride and add it to a beaker. Add 200mL of isopropanol to the beaker, stir evenly in the presence of isopropanol, then add 2mL of silane coupling agent KH-570 to the beaker, stir at a water bath temperature of 75°C, at a stirring speed of 250r / min, for 6h, evaporate the isopropanol completely, filter, wash with anhydrous ethanol, and then put it into a constant temperature dryer for drying. The dryer temperature is set to 80°C. After drying for 24 hours, modified silicon nitride is obtained;

[0082] Q3, uniform mixing: weigh 5g of modified nanoparticles and 10g of modified silicon nitride and add them to a beaker, add 20mL of anhydrous ethanol at the same time, perform ultrasonic treatment, the frequency of ultrasonic treatment is 300Hz, the time is 60min, after uniform dispersion, weigh 30g of polyurethane resin and add it to a beaker, then perform ultrasonic treatment, the frequency of ultrasonic treatment is 300Hz, the time is 60min, then add 30g of silicone resin to the beaker and stir evenly, continue ultrasonic treatment, the frequency of ultrasonic treatment is 300Hz, the time is 60min, and after uniform mixing, a homogeneous reaction liquid is obtained;

[0083] Q4. Add curing agent: add 4g of dibutyltin dilaurate as a reaction catalyst to the homogeneous reaction liquid, stir evenly, add 30g of isocyanate curing agent, stir evenly to obtain a liquid composite anti-corrosion coating, and apply it immediately;

[0084] Q5. Coating treatment: Spray the composite anti-corrosion coating on the surface of the passivated anchor metal rod with a coating thickness of 150μm. After drying for 24 hours, a corrosion-resistant and strong threaded steel resin anchor metal rod is obtained.

[0085] Comparative Example 1:

[0086] Compared with Example 3, in Comparative Example 1, in the preparation process of the corrosion-resistant and strong threaded steel resin anchor metal rod body, the composite anti-corrosion coating is not applied, and other conditions remain unchanged.

[0087] Comparative Example 2:

[0088] Compared with Example 3, in Comparative Example 2, in the preparation process of the corrosion-resistant and strong threaded steel resin anchor metal rod body, no zinc infiltration treatment is performed, and other conditions remain unchanged.

[0089] Comparative Example 3:

[0090] Compared with Example 3, in the preparation process of the corrosion-resistant and strong threaded steel resin anchor metal rod body, no passivation treatment is performed in Comparative Example 3, and other conditions remain unchanged.

[0091] Experimental example

[0092] The following performance tests were conducted on the corrosion-resistant and iso-strong threaded steel resin anchor metal rod bodies prepared in Examples 1-3 and Comparative Examples 1-3:

[0093] 1. Corrosion resistance test

[0094] The corrosion-resistant and equal-strength threaded steel resin anchor metal rod bodies prepared in Examples 1-3 and Comparative Examples 1-3 were tested in accordance with the implementation standard GB / T 10125-2012, with a test temperature of 35°C ± 2°C, a humidity of 66%, a salt spray deposition of 1.4 mL / h, and a salt spray pH of 6.5 to 7.2. The time for rust to appear was counted. The statistical results are shown in Table 1.

[0095] Table 1

[0096] Group Time (h) Example 1 2110 Example 2 2160 Example 3 2280 Comparative Example 1 1200 Comparative Example 2 1400 Comparative Example 3 1440

[0097] According to the statistical results of Table 1, it can be seen that the time for rust to appear in Examples 1-3 of the present invention is more than 2000 hours. Compared with Comparative Examples 1-3, the time for rust to appear in Examples 1-3 is significantly higher than that in Comparative Examples 1-3. The experiment shows that when preparing the metal rod body of the equal-strength threaded steel type resin anchor, coating the surface with a composite anti-corrosion coating and performing zinc infiltration and passivation process treatments can enhance the corrosion resistance of the metal rod body of the equal-strength threaded steel type resin anchor.

[0098] 2. Tensile strength test

[0099] The tensile strength of the corrosion-resistant equal-strength threaded steel resin anchor metal rod bodies prepared in Examples 1-3 and Comparative Examples 1-3 was measured according to the implementation standard GB / T 11968-2006. The measurement results are shown in Table 1.

[0100] Table 2

[0101] Group Tensile strength(MPa) Example 1 635 Example 2 641 Example 3 639 Comparative Example 1 634 Comparative Example 2 640 Comparative Example 3 640

[0102] According to the test results in Table 2, it can be seen that the corrosion-resistant equal-strength threaded steel resin anchor metal rod body prepared in Examples 1-3 of the present invention has no significant difference compared with Comparative Examples 1-3. The experiment shows that when preparing the equal-strength threaded steel resin anchor metal rod body, coating the surface with a composite anti-corrosion coating and performing zinc infiltration and passivation processes do not affect the tensile strength of the equal-strength threaded steel resin anchor metal rod body.

[0103] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

[0104] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a corrosion-resistant and iso-strong threaded steel resin anchor metal rod body, characterized in that: The steps include: (1) Steel pretreatment: Select the anchor metal rod steel, cut it and cut out the sharp corners to obtain the anchor metal rod workpiece; (2) Shot blasting: Put the anchor metal rod body into the shot blasting machine for shot blasting to obtain a clean anchor metal rod body; (3) Sherardizing treatment: the clean anchor metal rod body is placed in a sherardizing furnace and sherardized by powder sherardizing. After cooling, the metal rod body is taken out of the furnace to obtain a sherardized anchor metal rod body. (4) Passivation treatment: The zinc-plated anchor metal rod body is transported to the automatic spray cleaning area for cleaning, and then moved to the passivation area for passivation treatment. After the passivation treatment is completed, the residual passivation liquid is removed to obtain a passivated anchor metal rod body; (5) Applying a composite anti-corrosion coating: Applying a composite anti-corrosion coating on the surface of the passivated anchor metal rod body to obtain a corrosion-resistant and strong threaded steel resin anchor metal rod body.

2. The method for preparing a corrosion-resistant and iso-strong threaded steel type resin anchor metal rod body according to claim 1, characterized in that: In step (2), the shot blasting machine is of pass-through type, the diameter of the steel shot used is 0.8-1.2 mm, the shot blasting time is 20-30 min, and the surface cleanliness of the clean anchor metal rod body reaches Sa3 level.

3. The method for preparing a corrosion-resistant and iso-strong threaded steel resin anchor metal rod body according to claim 1, characterized in that: Step (3) is as follows: S1. Add filler: put the clean anchor metal rod into the sherardizing furnace, and then add the filler into the sherardizing furnace for embedding; S2. Adding the zincizing agent: Add zinc powder into the zincizing furnace and stir evenly; S3. High temperature zincizing: Sprinkle the zincizing agent evenly into the zincizing furnace and seal the furnace. Set the furnace temperature. After the reaction is completed, cool down and take the zincizing anchor bolt out of the furnace to obtain the zincizing anchor bolt metal rod body.

4. The method for preparing a corrosion-resistant and iso-strong threaded steel resin anchor metal rod body according to claim 3, characterized in that: The filler in S1 is one or both of quartz sand and alumina, and the volume of the added filler accounts for 35-40% of the volume of the zincizing furnace; the zinc powder in S2 is added at a ratio of 20-22kg / T of workpiece weight and stirred for 30-40min; the penetration aid in S3 is ammonium chloride, and ammonium chloride is added at a ratio of 0.3-0.35kg / T. The furnace temperature is set to 450-480℃, and the timing of insulation starts when the furnace temperature reaches 380℃, and the insulation time is 4-5 hours. The furnace is taken out when the temperature drops to 60-100℃.

5. The method for preparing a corrosion-resistant and iso-strong threaded steel resin anchor metal rod body according to claim 1, characterized in that: In step (4), the spraying time is 10 to 40 minutes, the pH value of the passivation solution is 10 to 12, the temperature of the passivation solution is 5 to 35° C., and the passivation time is 60 to 300 seconds.

6. The method for preparing a corrosion-resistant and iso-strong threaded steel type resin anchor metal rod body according to claim 1, characterized in that: Step (5) is as follows: Q1. Pretreatment of nanoparticles: put the nanoparticles into a flask, add silane coupling agent KH-570 in the presence of anhydrous ethanol, stir under water bath conditions, filter and wash, put into a constant temperature dryer for drying, and after completion, obtain modified nanoparticles; Q2. Silicon nitride pretreatment: Add silicon nitride to a beaker, stir evenly in the presence of isopropanol, then add silane coupling agent KH-570, stir in a water bath to completely evaporate the isopropanol, filter and wash, and put into a constant temperature dryer to dry, and after completion, modified silicon nitride is obtained; Q3. Mixing uniformly: Weigh the modified nanoparticles and modified silicon nitride into a beaker, add anhydrous ethanol at the same time, perform ultrasonic treatment, and after uniform dispersion, weigh the polyurethane resin and add it into a beaker, perform ultrasonic treatment, then add the silicone resin into the beaker and stir uniformly, continue ultrasonic treatment, and mix uniformly to obtain a homogeneous reaction liquid; Q4. Add curing agent: add catalyst to the homogeneous reaction liquid, stir evenly, then add curing agent, stir evenly to obtain liquid composite anti-corrosion coating; Q5. Coating treatment: Coat the composite anti-corrosion coating on the surface of the passivated anchor metal rod body, and after drying, obtain a corrosion-resistant and strong threaded steel resin anchor metal rod body.

7. The method for preparing a corrosion-resistant and iso-strong threaded steel type resin anchor metal rod body according to claim 6, characterized in that: The nanoparticles in Q1 are a mixture of nano-silica and nano-alumina, the mass ratio of nano-silica to nano-alumina is 2:1, the amount of anhydrous ethanol added is 10 to 15 times the volume of the nanoparticles, the amount of silane coupling agent KH-570 added is 1 to 10 mL, the water bath temperature is 70 to 75°C, the stirring speed is 200 to 250 r / min, the time is 4 to 6 hours, anhydrous ethanol is used for washing, the dryer temperature is set to 70 to 80°C, and the drying time is 24 to 30 hours.

8. The method for preparing a corrosion-resistant and iso-strong threaded steel type resin anchor metal rod body according to claim 6, characterized in that: In Q2, the mass ratio of silicon nitride added to nanoparticles is 2:1, the amount of silane coupling agent KH-570 added is 1-10 mL, the water bath temperature is 70-75°C, the stirring speed is 200-250 r / min, the time is 4-6 hours, anhydrous ethanol is used for washing, the dryer temperature is set to 70-80°C, and the drying time is 24-30 hours; in Q3, the amount of anhydrous ethanol added is 1-5 times the volume of modified nanoparticles and modified silicon nitride, the frequency of ultrasonic treatment is 200-300 Hz, the time is 30-60 min, the amount of polyurethane resin added is 1-3 times the mass of nanoparticles and silicon nitride, and the amount of silicone resin added is 0.8-2 times the mass of nanoparticles and silicon nitride.

9. The method for preparing a corrosion-resistant and iso-strong threaded steel type resin anchor metal rod body according to claim 6, characterized in that: The catalyst in Q4 is dibutyltin dilaurate, and the ratio of the amount of the catalyst added to the mass of the polyurethane resin is 1:5-10. The curing agent is an isocyanate curing agent, and the ratio of the amount of the curing agent added to the mass of the polyurethane resin is 1:1-2. The curing time is 2-6 hours. The coating method in Q5 is spraying, the coating thickness is 100-150 μm, and the drying time is 18-24 hours.

10. A corrosion-resistant and iso-strong threaded steel resin anchor metal rod body, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.